PENGENALAN KEGIATAN TAMBAHAN MATA PENCAHARIAN MASYARAKAT MELALUI PEMBINAAN PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT DI DESA PURBOSARI - Sri Yuwanti; Ahmad Mansur; Bagus Reza Hariyadi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2021)
This activity is a community service activity for the people of Purbosari village, Ngadirejo sub-district, Temanggung Regency. as part of the activities of the Central Java Province Bappeda for the 2017 fiscal year. The problem that is being handled is the problem of the loss of livelihoods of the tobacco farming community due to restrictions on tobacco farming and tobacco products. This activity is also an implementation of the Regulation of the Minister of Finance of the Republic of Indonesia Number: 28 / PMK.07 / 2016 concerning the Use, Monitoring and Evaluation of Tobacco Excise Production Sharing Funds. The model used is a community-based tourism development model as a form of the tourism sector's creative economy that provides optimal benefits to the community. The service process is carried out by means of efforts to empower the people's economy in the tourism sector with a community-based tourism (CBT) approach or community-based tourism by involving local communities in activities, which include the introduction of tourism potential and training on the utilization of local non-tobacco agricultural potentials to be processed into culinary products and by by tours. The local community is motivated to become the main actor in the management of tourism activities that arise from the utilization of the local potential that exists in the service location. The result of this activity is the achievement of community understanding of tourism as an alternative to activities other than tobacco farming, understanding of local tourism potential, development of tourism activities and tourism support activities in the location.